2016
DOI: 10.1021/acs.joc.6b01441
|View full text |Cite
|
Sign up to set email alerts
|

Formation of δ-Lactones by Cerium-Catalyzed, Baeyer–Villiger-Type Coupling of β-Oxoesters, Enol Acetates, and Dioxygen

Abstract: Formation of δ-lactones is observed when cyclopentanone-2-carboxylates are converted in a cerium-catalyzed reaction with α-aryl vinyl acetates under oxidative conditions. The products of this transformation possess a 1,4-dicarbonyl constitution together with a quaternary carbon center. Atmospheric oxygen is the oxidant in this process, which can be regarded as ideal from economic and ecological points of view. Further advantages of this new C-C coupling and oxidation reaction are its operational simplicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…[1] Very recently,w eh ave discoveredanew aerobic, cerium-catalyzed coupling reaction of enol acetatesa nd b-oxoesters leading to d-lactonesw ith an 1,4-dicarbonyl moiety in the side chain. [9] From am echanistic point of view,w ep roposet he initial formation of an endoper-oxidic1 ,2-dioxane derivative 6 by cerium-catalyzed coupling reactiono ft he two starting materials 1 and 2 and dioxygen. This recent discovery is based on our earlier work, where we found an ew route for the preparation of 1,4-diketones 5 by oxidative coupling of b-oxoesters like compound 1 with styrene.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[1] Very recently,w eh ave discoveredanew aerobic, cerium-catalyzed coupling reaction of enol acetatesa nd b-oxoesters leading to d-lactonesw ith an 1,4-dicarbonyl moiety in the side chain. [9] From am echanistic point of view,w ep roposet he initial formation of an endoper-oxidic1 ,2-dioxane derivative 6 by cerium-catalyzed coupling reactiono ft he two starting materials 1 and 2 and dioxygen. This recent discovery is based on our earlier work, where we found an ew route for the preparation of 1,4-diketones 5 by oxidative coupling of b-oxoesters like compound 1 with styrene.…”
Section: Introductionmentioning
confidence: 95%
“…[6] If unsymmetrically substituted ketones are submitted to the BVO, it is generally observed that the higher substituteda lkyl residue or-in cases of aryl ketones-the phenyl ring migrates. [9] With this work, we would like to uncover the origin of the unusual regiochemistry of the lactone formation, whichi s contrary to expectationsk nown from the BVO. [7] There are however very few exceptions from this regiochemistry.O ne of the prominentexamples for this opposite regiochemistryi st he lactone formed by BVO of camphor, [8] which wasr eported by Baeyerand Villiger themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the prefix “oxy” is used to represent all the “oxy”-ending groups, like in “oxymercuriation” for the addition of an acyloxy, alkyloxy or hydroxy group alongside a group with mercury to a double bond. “Oxycarbenium ion” can also be found in the literature with this meaning that it correctly describes the same intermediate, although not the more realistic representation of it [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Intra-and intermolecular processes are covered, The intermolecular addition of carboxylic acids to alkynes also presents enormous interest since the reaction products, i.e., enol esters (C or D in Scheme 2), are versatile building blocks in organic synthesis and material science. For example, to name just a few of their myriad applications, they are widely employed as mild acylating reagents [12,13], as monomers in diverse polymerization reactions [14][15][16], as substrates in asymmetric hydrogenation for the generation of enantioenriched alcohols [17][18][19], or as starting materials for different cross-coupling processes [20][21][22]. As for the cycloisomerization of alkynoic acids, a huge number of catalytic systems involving late transition metals have been described, with those based on ruthenium playing a prominent role [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%